BER-Optimized Precoders for OFDM Systems With Insufficient Cyclic Prefix - Bedi, Amrit S.; Akhtar, Javed; Rajawat, Ketan; Jagannatham, Aditya K. (IEEE communications letters, 2016)
This letter considers precoder design for orthogonal frequency division multiplexing (OFDM) systems with insufficient cyclic prefix (CP). Interference alignment is utilized to formulate the precoder design problem as a bit error rate (BER) minimization problem subject to a total power constraint. Subsequently, a novel closed-form solution is derived for the optimal precoder by exploiting Schur convexity and interference alignment-based interblock interference (IBI) suppression. The resulting precoder is also shown to be mean-square-error (MSE) optimal, and generalizes the existing designs. Closed-form expressions are also developed for quantifying the signal-to-noise ratio (SNR) gain of the proposed design over existing designs for practical channels with a decaying power-delay profile. Simulation results corroborate the performance improvements over existing MSE optimal designs considering the availability of both full and partial channel state information at the transmitter (CSIT) for various power delay profiles.